Carbon evolution and mixing effects on groundwater age calculations in fractured basalt, southwestern Idaho, U.S.A. - Schlegel, Melissa; Souza, Jennifer; Warix, Sara R.; Murray, Erin M.; Godsey, Sarah E.; Seyfried, Mark S.; Cram, Zane; Lohse, Kathleen A. (Frontiers in Water, 2024)
Using hydrochemical and isotopic compositions of springs and wells, we trace carbon from critical zone carbon dioxide (CO2) into groundwater of the semi-arid Reynolds Creek Experimental Watershed - Critical Zone Observatory, southwestern Idaho, USA. Dissolved inorganic carbon (DIC) concentrations, pH and stable isotope tracers of carbon for DIC (δ13CDIC), are used to show that most groundwater evolves under open system conditions, moving carbon into the groundwater and acting as a carbon sink. However, one sample (−10.94‰ δ13CDIC, 6,350 14C years before present (yrs. BP)) may have evolved under closed system conditions with a higher partial pressure of critical zone CO2 than present-day soils. By characterizing the carbon cycle, we show that (1) carbon evolution is primarily under open-system conditions, (2) shallow groundwater samples are generally less mixed and more recent (10 to 70 3H yrs. BP) than deeper groundwater samples (1,469 to 6,350 14C yrs. BP), and (3) the older portion of the groundwater may be even older than the calculated 14C ages, as indicated by the mixing of age tracers in intermediate wells. Our global conception of the deep critical zone should include carbon cycling of critical zone CO2 in old groundwater. Characterizing the deep critical zone in a semi-arid weathered silicate watershed improves our global understanding of carbon, nutrient and water cycling.